2005
DOI: 10.1038/labinvest.3700269
|View full text |Cite
|
Sign up to set email alerts
|

Vascular leakage in chick embryos after expression of a secreted binding protein for fibroblast growth factors

Abstract: Fibroblast growth factors (FGFs) have been implicated in a variety of physiologic and pathologic processes from embryonic development to tumor growth and angiogenesis. FGFs are immobilized in the extracellular matrix of different tissues and require release from this storage site to trigger a response. Secreted FGF-binding proteins (FGF-BPs) can release immobilized FGFs, enhance the activity of locally stored FGFs and can thus serve as an angiogenic switch molecule in cancer. Here, we report on the effect of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 44 publications
(46 reference statements)
1
24
0
Order By: Relevance
“…Furthermore, FGF-BP was responsible for enhancing FGF-2-mediated angiogenesis in a chick chorioallantoic membrane (CAM) assay (90). Overexpression of FGF-BP in a chicken transgenic model resulted in embryonic lethality due to massive disruption of blood vessel structure and integrity and subsequent hemorrhage (94). FGF-BP is expressed below the level of detection by Northern blotting in normal adult human tissues.…”
Section: Fibroblast Growth Factors and Fibroblast Growth Factor-bindimentioning
confidence: 99%
“…Furthermore, FGF-BP was responsible for enhancing FGF-2-mediated angiogenesis in a chick chorioallantoic membrane (CAM) assay (90). Overexpression of FGF-BP in a chicken transgenic model resulted in embryonic lethality due to massive disruption of blood vessel structure and integrity and subsequent hemorrhage (94). FGF-BP is expressed below the level of detection by Northern blotting in normal adult human tissues.…”
Section: Fibroblast Growth Factors and Fibroblast Growth Factor-bindimentioning
confidence: 99%
“…The chorioallantoic membrane (CAM) assay, used for more than half a century, has become a mainstay in the study of blood vessel development (Auerbach et al, 2003;Cruz et al, 2000;Cruz et al, 1997;DeFouw and DeFouw, 2000a;DeFouw and DeFouw, 2000b;Djonov et al, 2000a;Djonov et al, 2000b;McDonnell et al, 2005;Rizzo and DeFouw, 1996;Rizzo et al, 1995;Rizzo et al, 1993). The CAM assay has also proved useful for biological devices and in tissue engineering applications, particularly those concerning biocompatibility studies and angiogenic responses to tissue-engineered constructs (Borges et al, 2003a;Borges et al, 2003b;Nguyen et al, 1994;Ribatti et al, 2001;Rickert et al, 2003;Valdes et al, 2003;Valdes et al, 2002;Wong et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It was postulated that this would lead to creation of more mature blood vessels which would not "leak". The difference between tumour blood vessels and non-tumour angiogenesis is the ratio between VGF and FGF-1, the increased levels of FGF-1 leading to more mature blood vessel formation in normal healing processes [17]. This process has been the subject of clinical trials which have shown good results, but the principal problem has remained the lack of well controlled, adequately powered doubleblind controlled trials.…”
Section: Cytokine Mediated Angiogenesis For CLImentioning
confidence: 99%